Correlation between the severity of periodontitis and coronary artery stenosis in a Chinese population. (31st July 2013) - Yang, J; Feng, L; Ren, J; Wu, G; Chen, S; Zhou, Q; Du, Z; Zhang, S; Hu, C; Wu, X; Ling, L
Abstract: Background: The aim of this study was to evaluate the relationship between the severity of periodontitis and the extent and degree of coronary artery stenosis in a Chinese population. Methods: Patients (n = 853) with coronary artery stenosis confirmed by coronary angiography were eligible to take part in the study. Only subjects that were ≥60 years old, had ≥50% stenosis in at least one coronary artery, and did not have diabetes or a history of smoking were included (n = 115). After periodontal examination, including bleeding index, probing depth calculus index, plaque index and periodontal attachment loss, four groups were defined based on the severity of periodontitis: no periodontitis/gingivitis (M0, n = 19); mild periodontitis (M1, n = 27); moderate periodontitis (M2, n = 31); and severe periodontitis (M3, n = 38). The extent and degree of coronary artery stenosis was obtained by calculating the Gensini score (GS). Results: The GS was significantly greater in the M3 group compared with the M0 group. Multiple linear regression analysis revealed that probing depth and plaque index were significantly correlated with the GS. Conclusions: The extent and severity of coronary artery stenosis in Chinese patients ≥60 years old is positively correlated with the severity of periodontitis.